Worksop on Making Hand Sanitizers and Introduction to Assembling Sensor-Based Containers at SMK Yadika Pagelaran - Yanti, Demi Dama; Ayuwulanda, Aditya; Ghifari, M. Alvien; Nuroctaviani, Lety; Kurniawan, Rahmat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M), Institut Teknologi Sumatera, Lampung, Indonesia., 2023)
The Covid-19 pandemic, which has been endemic since the end of 2019, is still ongoing. Through the Decree of the Minister of Health of the Republic of Indonesia Number HK. 01. 07/MENKES/382/2020 concerning Health Protocols for the community in public places and facilities to prevent and control coronavirus disease 2019 (Covid-19. Schools are one of the pioneers in implementing government policies, in this case, Yadika Pagelaran Vocational High School, so the entire school environment must technically know how to prevent and control the coronavirus. Implementation of activities is held with face-to-face presentations on how to make hand sanitizers, followed by the practice of making hand sanitizers and the introduction of sensor-based hand sanitizer containers. The whole series of activities was well done. The initial test and post-test revealed that participants' knowledge of hand sanitizers increased from an average score of 64 to 80.44. This activity is vital to support the government in presenting schools that implement health protocols.